Novel functionalized polythiophene-coated Fe3O4 nanoparticles for magnetic solid-phase extraction of phthalates - Baharin, S.N.A.; Sarih, N.M.; Mohamad, S. (MDPI, 2016)
Poly(phenyl-(4-(6-thiophen-3-yl-hexyloxy)-benzylidene)-amine) (P3TArH) was successfully synthesized and coated on the surface of Fe3O4 magnetic nanoparticles (MNPs). The nanocomposites were characterized by Fourier transform infra-red (FTIR), X-ray diffractometry (XRD), Brunauer-Emmett-Teller (BET) surface area analysis, analyzer transmission electron microscopy (TEM) and vibrating sample magnetometry (VSM). P3TArH-coated MNPs (MNP@P3TArH) showed higher capabilities for the extraction of commonly-used phthalates and were optimized for the magnetic-solid phase extraction (MSPE) of environmental samples. Separation and determination of the extracted phthalates, namely dimethyl phthalate (DMP), diethyl phthalate (DEP), dipropyl phthalate (DPP), dibutyl phthalate (DBP), butyl benzyl phthalate (BBP), dicyclohexyl phthalate (DCP), di-ethylhexyl phthalate (DEHP) and di-n-octyl phthalate (DNOP), were conducted by a gas chromatography-flame ionization detector (GC-FID). The best working conditions were as follows; sample at pH 7, 30 min extraction time, ethyl acetate as the elution solvent, 500-μL elution solvent volumes, 10 min desorption time, 10-mg adsorbent dosage, 20-mL sample loading volume and 15 g L-1 concentration of NaCl. Under the optimized conditions, the analytical performances were determined with a linear range of 0.1-50 μg L-1 and a limit of detection at 0.08-0.468 μg L-1 for all of the analytes studied. The intra-day (n = 7) and inter-day (n = 3) relative standard deviations (RSD%) of three replicates were each demonstrated in the range of 3.7-4.9 and 3.0-5.0, respectively. The steadiness and reusability studies suggested that the MNP@P3TArH could be used up to five cycles. The proposed method was executed for the analysis of real water samples, namely commercial bottled mineral water and bottled fresh milk, whereby recoveries in the range of 68%-101% and RSD% lower than 7.7 were attained.